Characterization of Fungi at Daycare Centers: A Systematic Review - S.K, Yusof; Norhidayah, Abdull; Nurud Suria, Suhaimi; Afiza, Abdullah Suhaimi; M., Zahaba; I., Ismail (AIP Conference Proceedings, 2024)
Exposure to indoor airborne fungi may cause the occupant to get allergy reactions and asthma symptoms. Children may be more susceptible to the adverse effects of airborne fungi than adults due to their age and vulnerability. This study systematically reviews the characterization of fungi and the parameter affecting the characteristic of fungi at daycare centers. This systematic literature review used PRISMA (Preferred Reporting Items for Systematics Review and Meta-Analyses). All the articles related to the characterization of fungi at daycare centers published from 2011 to 2021 were analyzed and reviewed from an electronic database such as Google Scholar, Science Direct, Scopus, Taylor & Francis and SpringerLink. In this systematic review, fifteen studies that complied with the inclusion and exclusion criteria were chosen for the review. The median value of indoor fungi concentration from included studies was 317.25 CFU/m³ and ranged from 3.4 CFU/m³ (in Khorramabad, Iran, in July) to 47 581 CFU/m³ (in Taiwan). The findings indicate that Penicillium, Cladosporium, and Aspergillus are typically observed in daycare facilities. This review aims to present a thorough overview of the current understanding of the characterization of fungi at daycare centers and help researchers determine their focus areas when conducting studies in this field.